Theodore Edgar St. John papers - St. John, Theodore Edgar, 1831-1887.
Volume consisting chiefly of letters (1862-1865) written by St. John to Jane Ceeclia Harries (St. John), whom he later married, while he served with the 14th Wisconsin Infantry in northern Mississippi (1862) and later in the Vicksburg, Atlanta, Savannah, and Carolinas campaigns. Also includes discharge papers, orders, pension records, biographical notes, and a poem written by a member of Gen. James Birdseye McPherson's staff upon the general's death.
Positive photocopies of, in part, handwritten and typewritten transcripts.
Civil War soldier of Mascoda, Wis.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: McPherson, James Birdseye, -- 1828-1864 -- Death and burial; St. John, Jane Cecilia Harries, -- 1843-1927 -- Correspondence; United States. -- Army. -- Wisconsin Infantry Regiment, 14th (1862-1865); Atlanta Campaign, 1864; Georgia -- History -- Civil War, 1861-1865.; Mississippi -- History -- Civil War, 1861-1865.; North Carolina -- History -- Civil War, 1861-1865.; Savannah (Ga.) -- History -- Siege, 1864.; South Carolina -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Campaigns; Vicksburg (Miss.) -- History -- Siege, 1863.; Wisconsin -- History -- Civil War, 1861-1865.; Soldiers